A Fonte dos Metais da Mina de Ouro do Schramm, Santa Catarina: Evidências de Dados de Isótopos de Pb e Elementos Terras Raras - DA ROCHA, FLÁVIO FRANÇA NUNES; NETO, ARTUR CEZAR BASTOS; REMUS, MARCUS VINÍCIUS DORNELLES; PEREIRA, VITOR PAULO (Pesquisas em Geociências, 2005)
<!-- .p { text-align: justify; } --> The source of the ore elements in the Schramm gold mine, localized in central part of Santa Catarina shield, has been constrained based on lead isotope composition of galena and sulfosalts, and the rare earth element (REE) patterns of the ore. The Pb207/ Pb206 model age obtained in galena and lillianite-gustavite series from the mineralization yields an age of 1.88 Ga. It is higher than the estimated age of the deposit (» 534 Ma). The Pb isotopic composition obtained in these minerals indicates that the age of Schramm mine source is similar to that of the galena of the Ribeirão da Prata mine (Pb-Zn-Cu-Ag). This mine is located 25 Km southwest of the Schramm gold mine witch is hosted in the tension fracture zone conjugated with the first order shear zone that contains the Ribeirão da Prata deposit. The similarities between Pb-isotope compositions of both deposits could indicate that they were contemporaneous and derived from the same regional lead source. The REE patterns of the ore samples of Schramm mine are similar to that of the pyroxenites and banded iron formations from the Archean Santa Catarina Granulitic Complex that host the Schramm gold mine. They present low REE contents with flat patterns and lack Eu anomalies. The comparison among the isotopic data from this mine with those from other places indicates that the banded iron formation and mafic-ultramafic granulitic gneisses are the source of the gold mineralization. This evidence agreed with the hypothesis that the ore fluids were derived from retrogressive metamorphism reactions of Santa Catarina Granulitic Complex in the shear zones during the final stage of Brasiliano orogenic cycle.